Test of Some Kind of Biomass Fuels on Processed Waste Polymer Agriculture Tool - Herdianze Novalina Pasaribu; Saipul Bahri Daulay; Adian Rindang (Universitas Sumatera Utara, 2015)
Indonesia has many sources of renewable energy. One of them is biomass. This research was carried out to try some fuel from biomass to be used in agricultural polymer waste equipment. Biomass which used in this research were candlenut shell, coconut shell, and wood. Parameters used were equipment effective capacity, the percentage of polypropylene plastic residue, the percentage of fuel residue, oil volume, melting point, and the melting time. The results were: equipment effective capacity for candlenut shell fuel, coconut shell fuel, and wood fuel were 0 ml/hour, 62,22 ml/hour, and 77,66 ml/hour respectively. The percentage of plastic residue generated for candlenut shell, coconut shell, and wood fuel were 53.33%, 22.67%, and 20% respectively. The percentage of residue fuel for candlenut shell fuel, coconut shell fuel, and wood fuel were 35.67%, 16.87%, and 16% respectively. The volume of oil produced for candlenut shell fuel, coconut shell fuel, and wood fuel were 0 ml, 93.33 ml, and 110 ml respectively. The melting point obtained from the burning of fuel wood and coconut shell was 250 0C and the candlenut shell fuel was 175 0C. Melting time resulted in fuel of candlenut shell, coconut shell, and wood were 3.1 hours, 1.5 hours, and 1.44 hours respectively. Keywords : Biomass fuel, Plastic waste, and Pyrolysis.